The Analysis of Negotiation of Meaning Strategy Used by English Teacher in Classroom Interaction - Lidya Rahmah; Endang Komariah; Iskandar Abdul Samad (Universitas Syiah Kuala, 2020)
This paper reports on analysis the negotiation of meaning strategy employed by English teacher in classroom interaction. This qualitative research conducted at SMAN 3 Banda Aceh. The result of the research showed that the second-grade English teacher used negotiation of meaning strategy in which appeared in different amount and frequency. Trigger appeared as the most frequent component of negotiation of meaning strategy produced by the teacher during the interaction, meanwhile, self-modification of response (SMR) is the most significance way the teacher response the students’ signal in negotiating the conversation. In the wake of conducting this research, bringing negotiation of meaning strategy in dealing with communication impasses in the classroom in exceptionally proposed for both teacher and EFL students.